PERBEDAAN EFEKTIVITAS EDUKASI BEYOND USE DATE MELALUI BUKU SAKU DAN VIDEO TERHADAP TINGKAT PENGETAHUAN - Veronica, Elsa Ignatia; Arrang, Sherly Tandi; Notario, Dion (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
The stability of drug preparations is very important to maintain because it can affect the quality, effectiveness, and safety of these drug preparations. If the product's primary packaging is opened, the stability of the preparation is changed. The product's stability duration is correlated with the expiration date. The expiration date of the product after opened from its original packaging or mixed with other preparations is known as the beyond-use date (BUD). Research on the level of public knowledge about BUD still needs to be improved, and the results of several studies show that the community needs to learn and understand BUD. Therefore, a study was conducted to assess differences in the effectiveness of educational media (pocketbook and video) on knowledge related to BUD. Quasi-experimental research design with the type of pre-test & post-test two groups. The number of respondents in this research was 70, divided into two: pocketbooks (35 respondents) and videos (35 respondents). Based on the analysis results, it was found that there was a change in the respondents' knowledge after being given education. As many as 60% of respondents in the pocketbook group had insufficient knowledge before being given education, and after being given education, 74% of respondents had good knowledge (p=0.01). In the video group, there was an increase in the good knowledge respondent group; namely, before being given education, the number was 37%, increasing to 43% after being given education (p=0.01). The regression analysis showed that educational media significantly influenced respondents' knowledge related to BUD (p=0.04). The ducation with a pocketbook and video increases knowledge about BUD, but videos provide a better increase in knowledge.